2020
DOI: 10.1002/aoc.5958
|View full text |Cite
|
Sign up to set email alerts
|

Controllable construction of Ce‐Mn‐Ox with tunable oxygen vacancies and active species for toluene catalytic combustion

Abstract: A series of Ce‐Mn‐Ox catalysts synthesized under different hydrothermal conditions were evaluated by catalytic removal of toluene. The results of characterization showed that the contents of oxygen vacancies and active species in catalysts were crucial for the catalytic oxidation process. The concentration of Ce3+, Mn3+, and adsorbed oxygen associated with structural defects in Ce‐Mn‐Ox catalysts could be controlled by hydrothermal conditions, which were considered to promote redox capacity and improve catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…Therefore, the experimental results were consistent with the literature [34] . Mn 3+ promoted the diffusion of oxygen and the generation of crystal defects, thereby enhancing the activity of the catalyst [31,65–67] …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the experimental results were consistent with the literature [34] . Mn 3+ promoted the diffusion of oxygen and the generation of crystal defects, thereby enhancing the activity of the catalyst [31,65–67] …”
Section: Resultssupporting
confidence: 89%
“…[34] Mn 3 + promoted the diffusion of oxygen and the generation of crystal defects, thereby enhancing the activity of the catalyst. [31,[65][66][67] Figure 6 (c) reflected the oxygen species on the surface of the catalyst, and it can be seen that the O 1s spectra were deconvoluted into two obvious peaks, with binding energies of 529.5-530.1 eV and 531-531.7 eV corresponding to lattice oxygen (O latt ) and adsorbed oxygen (O ads ), respectively. [68,69] According to the calculation and summary in Table 2, O ads /O latt changed according to the following: Ce 3 MnO X -10.5 (1.34) > CeMnO X -10.5 (0.63) > CeMn 2 O X -10.5 (0.56) > CeMnO X -8 (0.53) > CeMnO X -6 (0.46).…”
Section: Surface Chemical Propertiesmentioning
confidence: 99%
“…A clear peak located at 462 cm −1 increased its intensity as Ce content augmented. This signal corresponds to a symmetrical stretching vibration resulting from the atoms around Ce 4+ ions in the CeO 2 fluorite type structure [9,20,22] . The second signal at 642 cm −1 was assigned to the characteristic Mn−O stretching mode [9,20,22] .…”
Section: Resultsmentioning
confidence: 96%
“…Figure b shows the XPS spectra for O 1s. According to the peak-fitting deconvolutions, O 1s was divided into three characteristic peak segments at 529.8, 531.4, and 533 eV, which were attributed to the surface lattice oxygen (O latt ), adsorbed oxygen species (O ads ), and surface adsorbed hydroxyl species (O sur ), respectively. , The O 1s spectrum also showed that the adsorbed oxygen content increased gradually with increasing Ce content because of Ce doping, producing active oxygen species. Figure c shows the Mn 2p spectra of the different catalysts.…”
Section: Resultsmentioning
confidence: 99%